Neologia formal: uma abordagem pedagógica dos processos deformacionais de criação de palavras no português brasileiro - Nágila Sabrina dos Reis Santos (2024)
This investigation aimed to analyze teaching materials, such as textbooks and school grammars, to observe the pedagogical approach of neology, mainly about neologisms formed by deformational processes. The hypothesis was that there was a gap in the teaching of the Portuguese language in Basic Education regarding the treatment of this lexical area. Furthermore, we sought to collect neologisms formed by deformational processes in advertising texts in digital media, to observe the productivity of such processes in the creation of new words. To form the corpus of analysis with advertising texts, three social networks were selected – Instagram, Facebook and Twitter. We sought to observe how different advertisers use deformational neologisms as persuasive resources to influence consumers. Finally, pedagogical proposals that articulate the morphosyntactic and the semantic-pragmatic bias were developed as a way of promoting a pedagogical approach to the deformational processes of lexical creation based on the didacticization of the advertising genre to allow analysis and critical reflections on the part of students. For the development of this research, different works were carried out to support the concepts considered here and the methodology, such as Alves (1990), about the concepts of neology and neologism, Ferraz (2006), about the social issue involving the neological area and the criteria for verifying neologisms, Ferraz (2020), to define the deformational processes of word constitution, Travaglia (2021), regarding the role of the school in the development of the student's lexical competence and the production of pedagogical activities, among others authors. The methodological processes of this study are hypothetical-deductive and qualitative in nature, developed in five stages: analysis of teaching materials, collection of neologisms in digital media, verification of neologisms using lexicographic criteria, analysis of selected neologisms and preparation of didactic proposals. With this study, the aim was to promote exercises that favor the approach of deformational neologisms in Portuguese language classes as a way of demonstrating the extralinguistic issues that involve lexical innovations.